Comparison of Postoperative Analgesic Profiles Between Transversus Abdominis Plane Block and Local Wound Infiltration in Living Donor Kidney Transplantation Recipients: A Propensity Score-Matched Analysis - Min Suk Chae; Kyung Kwan Lee; Jin-Oh Jeong; Wonwoo Jeong; Young Wook Moon; Ji Young Min (Life)
Effective postoperative pain management is crucial for optimizing recovery and clinical outcomes in living donor kidney transplantation (LDKT). This retrospective study compared the efficacy and safety of transversus abdominis plane (TAP) block and local wound infiltration (LWI) for postoperative analgesia. A total of 524 LDKT recipients, matched through propensity scoring, were analyzed (262 per group). Pain intensity was assessed using the visual analog scale (VAS) at multiple postoperative time points, while opioid consumption was evaluated based on intravenous patient-controlled analgesia (IV-PCA) usage and rescue fentanyl doses. The TAP block group had significantly lower VAS pain scores at 1, 4, and 8 h postoperatively (p < 0.001) and required fewer opioids, as evidenced by reduced IV-PCA usage (55.9 ± 10.2 mL vs. 69.7 ± 18.2 mL; p < 0.001) and lower rescue fentanyl doses (67.7 ± 30.6 µg vs. 119.1 ± 71.8 µg; p < 0.001). Despite these differences in analgesic efficacy, no significant differences were observed between the groups in terms of postoperative nausea and vomiting or complications such as systemic toxicity and nerve injury. These findings suggest that the TAP block provides more effective early postoperative pain relief and reduces opioid requirements without increasing adverse events. Given its favorable safety profile and effectiveness, the TAP block is a valuable component of multimodal analgesia in LDKT recipients, supporting enhanced recovery while minimizing opioid-related complications.